Respuesta :
Answer:
Ok, we have the line:
y = k*x + 1
And we know that the point (1, 3) belongs to this line.
This means that when x is equal to 1, y must be equal to 3.
Then:
3 = k*1 + 1
3 - 1 = k
2 = k
Now we know that our line is:
y = 2*x + 1.
And we can graph it, as shown below.
![Ver imagen facundo3141592](https://us-static.z-dn.net/files/da2/811a1a2890bb723df05212f01680fe67.png)
Answer:
y = 2x + 1
First coordinate: (0, 1)
Second coordinate: (2, 3)
![Ver imagen nanidesuka](https://us-static.z-dn.net/files/d9c/d769251b5e1e1ca9d009080943e20909.png)